2003
DOI: 10.1038/sj.onc.1206170
|View full text |Cite
|
Sign up to set email alerts
|

Common fragile sites are preferential targets for HPV16 integrations in cervical tumors

Abstract: The development of cervical cancer is highly associated with human papillomavirus (HPV) infection. HPV integration into the genome of infected cervical cells is temporally associated with the acquisition of the malignant phenotype. A relationship between the sites of HPV integration in cervical cancer and the position of the common fragile sites (CFSs) has been observed at both the cytogenetic and molecular levels. To further explore this relationship at the molecular level, we used RS-PCR to rapidly isolate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
204
3
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(225 citation statements)
references
References 59 publications
15
204
3
3
Order By: Relevance
“…Extensive analyses of retrovirus integration sites have shown that active genes (Schroder et al, 2002) or transcription start regions (Wu et al, 2003) are preferential integration targets. Fragile sites have also been reported to facilitate HPV DNA integration (Thorland et al, 2003), but other factors may influence the nature of the genetic rearrangements that implicate insertion of foreign DNA and illegitimate recombination. In Burkitt lymphoma, the frequency of the different types of translocation observed was highly correlated with the probability that the two partners were in physical proximity in the cell nucleus (Roix et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive analyses of retrovirus integration sites have shown that active genes (Schroder et al, 2002) or transcription start regions (Wu et al, 2003) are preferential integration targets. Fragile sites have also been reported to facilitate HPV DNA integration (Thorland et al, 2003), but other factors may influence the nature of the genetic rearrangements that implicate insertion of foreign DNA and illegitimate recombination. In Burkitt lymphoma, the frequency of the different types of translocation observed was highly correlated with the probability that the two partners were in physical proximity in the cell nucleus (Roix et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism could be related to the stimulation of host cell cycle, inhibition of cellular apoptosis, cell growth, and escape from the host immune system, leading to cellular proliferation in multistep tumorigenesis. It has also been reported that HPV integration occurs in chromosomal fragile sites (Thorland et al, 2003). Common fragile sites are thought to be highly unstable and preferential sites for translocations, deletions, intrachromosomal gene amplification, and integration of plasmid DNA and tumor viruses, such as SV40 (Smith et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cell cultures have shown that under replication stress conditions fragile sites are hotspots for sister chromatid exchange, translocations and deletions (Glover and Stein, 1987;Glover and Stein, 1988;Wang et al, 1997). In vivo, fragile sites correlate with chromosomal breakpoints in tumors (Hecht and Hecht, 1984;Yunis and Soreng, 1984) and with integration sites of oncogenic viruses (Thorland et al, 2003;Bester et al, 2006).…”
Section: Introductionmentioning
confidence: 99%